DAYA TARIK WISATA MASJID RAYA AN-NUR KOTA PEKANBARU PROVINSI RIAU - Azizah, Nur’ Aini; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to find out how the An-Nur Grand Mosque attracts tourists to visit. This research was conducted at the An-Nur Grand Mosque, Pekanbaru City, Riau Province. This research uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data obtained directly from the field. This research uses data collection techniques from observation, documentation and interviews. From this research it can be seen that the An-Nur Grand Mosque is one of the main religious tourist attractions in Pekanbaru City, Riau. This mosque not only functions as a place of worship, but also as a center for social and cultural activities for the local community and visitors from outside the area. An-Nur Grand Mosque is renowned for its magnificent architecture that combines Middle Eastern, Indian and Malay architectural elements, creating a stunning and iconic structure Keywords: An-Nur Grand Mosque, religious tourism, architecture, culture, Pekanbaru, Riau.